2015
DOI: 10.5014/ajot.2015.014605
|View full text |Cite
|
Sign up to set email alerts
|

Client and Therapist Perspectives on the Influence of Low Vision and Chronic Conditions on Performance and Occupational Therapy Intervention

Abstract: Both vision loss and comorbidities influence occupational performance, supporting the need for interventions to address both conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Of these 9 were focused on Indigenous older adults so for this review, a total of 36 articles were included. Thirty studies were qualitative studies [ 26 55 ], four were cross-sectional studies [ 56 59 ], one was mixed method study [ 60 ] and one was a secondary qualitative data analysis [ 61 ] (Table 1 ). Twenty two studies were conducted in North America [ 26 , 28 30 , 33 , 35 , 37 , 38 , 41 , 43 , 46 52 , 55 , 57 60 ], ten in Europe [ 31 , 32 , 34 , 39 , 40 , 44 , 45 , 54 , 56 , 61 ] and three in Australia/New Zealand [ 27 , 42 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these 9 were focused on Indigenous older adults so for this review, a total of 36 articles were included. Thirty studies were qualitative studies [ 26 55 ], four were cross-sectional studies [ 56 59 ], one was mixed method study [ 60 ] and one was a secondary qualitative data analysis [ 61 ] (Table 1 ). Twenty two studies were conducted in North America [ 26 , 28 30 , 33 , 35 , 37 , 38 , 41 , 43 , 46 52 , 55 , 57 60 ], ten in Europe [ 31 , 32 , 34 , 39 , 40 , 44 , 45 , 54 , 56 , 61 ] and three in Australia/New Zealand [ 27 , 42 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…We sought information from older adults with MCC, their caregivers and health care providers about needs of older adults with MCC and some researchers included more than one perspective in their studies [ 26 , 31 , 34 , 38 , 40 42 , 44 , 46 , 50 , 53 , 60 ]. Thirty-four studies included participants with MCC [ 26 , 27 , 29 38 , 40 53 , 55 61 ] and the sample size ranged from 8 [ 60 ] to 1274 participants [ 58 ] with a total of 3058 participants in the studies. Seven studies included caregivers of older adults with MCC [ 31 , 38 , 41 , 42 , 44 46 ] and the sample sizes varied from 8 [ 42 ] to 33 [ 31 ] with a total of 137 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Barstow, Warren, Thaker, Hallman, and Batts (2015) found that clients with MCCs experience a loss of independence in self-care and of safe participation in desired social and leisure activities. These losses are further exacerbated by the psychosocial implications of a new diagnosis: People have reported feeling a loss of control over their own life, a theme reflected across multiple client populations (Brereton & Nolan, 2000; Pyatak, 2011; Wood, Connelly, & Maly, 2010).…”
Section: Prevalence and Impact Of Multiple Chronic Conditionsmentioning
confidence: 99%